ILLEGAL MIGRATIONS OF POPULATION IN LIBYA - Fathija Abdusalam Ibn Arabi (Pravo, 2015)
THE migrations go far back into history, up to the emergence of a mankind itself. They are expressed by a man`s constant movement from one place to another, without a limitation and interference in his search of safety or by his escape from nature and weather conditions. The motivation and driving force for this is the will to survive, preserving and extending the life of the species or the desire to discover the environments more suitable and responsive to his needs and aspirations. Libya is among the countries that have severely been affected by the process of illegal migrations. They are caused by the inﬂuence of two main factors, one of which refers to a geographical position and the other one is connected with an envious standard of living of the citizens of Libya in relation to the countries in its neighborhood. According to the aforementioned facts, in the paper there will be presented both theoretical frameworks and practical experiences the author had during his life and work in Libya.